Simplification of wastes for a warehouse using Boolean logic: A conceptual paper - Sarifudin, M. S.; Mansor, M. A. (Taylor's University, 2019)
Warehouse accumulate wastes consisting of inventory, waiting and transportation. However, the existence of warehouse will increase the operation expenditure and can lead to profit losses. Therefore, manufacturers need to identify and minimize wastes to reduce the consumption of resources and keep minimum inventory in the warehouse. Value Stream Mapping (VSM) is an approach to minimize waste. This tool visualizes the information and material flow of manufacturing activities. The development of a model based from VSM determined the current state of wastes in a warehouse. From the information flow, the optimum combination of wastes was determined through Boolean concept. The wastes are simplified and combined by passing through the Boolean operators consist of AND Gate and OR Gate. The outcomes of this paper is to propose a conceptual model of new VSM to identify and minimize wastes in a warehouse. At the same time, to propose a method that can cater for time consumed in every activity which differs from one station to another.